2011
DOI: 10.1590/s1517-83822011000400039
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of potential lactic acid bacteria (LAB) from freshwater fish processing wastes for application in fermentative utilisation of fish processing waste

Abstract: Proteolytic and/or lipolytic lactic acid bacteria (LAB) were isolated from visceral wastes of different fresh water fishes. LAB count was found to be highest in case of visceral wastes of Mrigal (5.88 log cfu/g) and lowest in that of tilapia (4.22 log cfu/g). Morphological, biochemical and molecular characterization of the selected LAB isolates were carried out. Two isolates FJ1 (E. faecalis NCIM5367) and LP3 (P. acidilactici NCIM5368) showed both proteolytic and lipolytic properties. All the six native isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
3
Order By: Relevance
“…Así mismo, la adición de CP probablemente aumentó la actividad de la pepsina utilizada en el segundo paso de la prueba de digestibilidad, lo cual simula la digestión estomacal y por tanto la DIVMS de los ensilados aumentó. Las BAL son mejor conocidas como cultivos iniciadores debido a sus características metabólicas versátiles tales como actividad acidificante, actividad proteolítica y síntesis de bacteriocinas (Jini et al, 2011). En general, la DIVMS de los ensilados fue mayor con Lactobacillus B2 que con Lactobacillus sp., debido al mejor poder acidificante de Lactobacillus B2 y probablemente a una alta capacidad productora de enzimas digestivas.…”
Section: Composición Químicaunclassified
See 2 more Smart Citations
“…Así mismo, la adición de CP probablemente aumentó la actividad de la pepsina utilizada en el segundo paso de la prueba de digestibilidad, lo cual simula la digestión estomacal y por tanto la DIVMS de los ensilados aumentó. Las BAL son mejor conocidas como cultivos iniciadores debido a sus características metabólicas versátiles tales como actividad acidificante, actividad proteolítica y síntesis de bacteriocinas (Jini et al, 2011). En general, la DIVMS de los ensilados fue mayor con Lactobacillus B2 que con Lactobacillus sp., debido al mejor poder acidificante de Lactobacillus B2 y probablemente a una alta capacidad productora de enzimas digestivas.…”
Section: Composición Químicaunclassified
“…Durante la fermentación las BAL incrementan la producción de ácidos, principalmente láctico, por lo que el pH disminuye y se frena el deterioro microbiano; además las proteasas del pescado se activan, aceleran la proteólisis y por consecuencia la digestibilidad del producto aumenta (Ghaly et al, 2013). Así mismo, las BAL generan compuestos tales como bacteriocinas y peróxido de hidrógeno que ayudan a la conservación y diacetilo, sustancia potenciadora de aroma y sabor (Jini et al, 2011). En ese sentido, para lograr el control de la fermentación es importante la selección de cepas de BAL.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The increase in lactic acid bacteria counts were observed in groups FA and FASA during storage. Jini et al, (2011) reported that lactic acid bacteria counts in visceral wastes of different freshwater fishes were found in the range of 4.22-5.88 log cfu g -1 . Similarly, lactic acid bacteria counts were found in range of 4.50-5.68 log cfu g -1 in this study (Figure 2).…”
Section: Microbiological Assessmentmentioning
confidence: 99%
“…LAB are generally associated with habitats rich in nutrients such as, various food products (milk, meat, vegetables), fermented, decaying material and the mucosal surfaces of the gastrointestinal tract of animals (Salminen and Wright, 2004). They are the most common type of microbes used as probiotics which are safely applied in medical and veterinary functions (Rauta et al, 2013). Also, with the demand for environmental friendly aquaculture, microbial interventions of such indigenous LAB in form of probiotic treatments is on rise as they may provide broad spectrum and greater non-specific disease protection (Balcazar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%